Analisis Kebijakan Turki Dalam MoU (Memorandum of Understanding) Terkait Delimitasi Batas Maritim Dengan Libya Tahun 2019 - Dinata, Made Mustika Sastra; Priadarsini, Ni Wayan Rainy; Parameswari, Anak Agung Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 2 (2024): JURNAL DIKSHI, 2024)
The history of maritime disputes between Turkey and Greece has been going on for 5 decades. The increasing complexity in resolving the maritime boundary issue between the two occurred when Turkey changed its foreign policy approach to become more assertive and pro-active in maintaining its EEZ/continental shelf claims.Turkey initiated maritime boundary delimitation agreement with Libya in 2019, which is considered to violate international law because it ignores Greece EEZ/continental shelf claim. Greece with the support of other regional actors responded negatively to the agreement. This has an impact on Turkey’s isolated position in the region and Turkey is assumed has turned into a revisionist state. Based on the explanation above, this research aim to identify the determinant of foreign policy that influence Turkey’s policy in initiating MoU on maritime boundary delimitation with Libya. This research used qualitative-descriptive approach by adopting the concept of determinant of foreign policy and bilateral agreement as analytical tool. The results of this research has found several determining factor that influence Turkish policy, namely :(1) Political Ideology of President Recep Tayyip Erdogan,(2) Coallition of AKP party – MHP party, (3) Turkey’s energy diversification strategy, (4) Greece’s geopolitical vision to become a regional energy hub